"Diseño de un proceso de producción y comercializ<ación de adoquines decorativos para parques y patios, a base de polvillo de caucho recliclados y resina, en la ciudad de Quevedo - Salinas Montenegro, Ricardo Alberto (2019)
The objective of this research is to carry out the economic technical study for the creation of a plant to produce cobblestones for parks and courtyards in the canton of Quevedo, for research purposes, a survey was conducted that sampled the small vulcanizing artisans and the companies engaged in the sale and installation of tyres in Quevedo, resulting in the guangzhou not having an adequate process for disposing of tyres, with a quantity of 2100 monthly tires being discarded at the time of the municipal dump by these artisans and companies. Within the technical study, the location of the project was established on the Quevedo-El Empalme KM9 Recinto San Luis Mocache road within the road circle of Quevedo, a capacity of the plant was estimated at 300 kilos of tyres per hour; In addition, to carry out the functional organization chart, the production process was defined with its respective flowchart, which indicates the consecutive steps of tyre recycling out of use. The calculation of the civil construction of 1500 m2 within this area was also carried out, warehouses of finished product and raw materials (NFU) offices and production area were estimated. The distribution of the plant of machinery and equipment, offices etc. was established. The economic study determined the investment of the $286092.52 project and includes items such as: machinery, Civil works, loans, working capital and 3% of contingencies, the annual expenses and annual incomes that served as the basis for effective cash flow were established, within the financial indicators was determined: the positive VAN of $2167082.20, the TIR 28.56 %, the profit/cost ratio at 1.30. Based on these results it was established that the project is technically and economically profitable and positively influences the environment of the canton of Quevedo. Keywords: Decorative cobblestones, recycling, resin, production.